(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the significance of personal and social values as a psychological filter for information selection in students. Today, as the flow of digital information is rapidly increasing, students rely on psychological mechanisms formed under the influence of the system of individual values and the social environment when sorting information. The article analyzes the concept of the psychological filter, the factors influencing its formation, as well as the role of personal and social values in this process. The research results show that values are an important psychological tool in the selection and perception of information. This emphasizes the need for a value-based approach to improving information literacy.